Incidence of infant mortality and its predictors in East Africa using Gompertz gamma shared frailty model - Getayeneh Antehunegn Tesema; Beminate Lemma Seifu; Zemenu Tadesse Tessema; Misganaw Gebrie Worku; Achamyeleh Birhanu Teshale (BMC, 2022)
Abstract Background Globally, infant mortality is a major public health concern and a sensitive indicator of countries' socio-economic and health status. Despite the substantial reduction of under-five mortality in sub-Saharan African countries specifically in East Africa, the infant mortality rate remains highest and too far below to achieve the WHO target. As to our search of the literature is concerned, there is a dearth of evidence on the incidence and predictors of infant mortality in East Africa. Therefore, this study investigated the incidence of infant mortality and its predictors in East Africa. Methods The present study has utilized 138,803 weighted samples from Demographic and Health Surveys (DHSs) of 12 East African countries. Considering the hierarchical nature of DHS data shared frailty parametric survival models were fitted and compared based on deviance (-2LLR), AIC, and BIC. Gompertz gamma shared frailty model was the best-fitted model for the data since it had the lowest deviance, AIC, and BIC values. Variables with a p-value < 0.2 in the bi-variable analysis were considered for the multivariable analysis. In the multivariable Gompertz gamma shared analysis, the Adjusted Hazard Ratio (AHR) with 95% Confidence Interval (CI) was reported to declare the significant predictors of infant mortality. Results The infant mortality rate in East Africa was 41.41 per 1000 live births. Mothers aged 25-34 years, wanted birth, health facility delivery, 1-3 ANC visit, being 2nd- 4th birth order, 5th and above, the birth interval of 24-48 months, and birth interval of 49 months and above were significantly associated with lower risk of infant mortality. Whereas women who didn't have formal education, women who didn't participate in making health care decisions making, being male children, cesarean delivery, small size at birth, and large size at birth were significantly associated with a higher risk of infant mortality. Conclusion Despite the substantial progress in improving maternal and child health, this study showed that infant mortality is still a major public health concern in East Africa. Maternal age, place of delivery, maternal education, birth size, sex of the child, mode of delivery, women's autonomy, birth order, birth interval, and ANC visit were found to be significant predictors of infant mortality. Therefore, public health interventions enhancing health facility delivery, ANC visit, maternal education, birth spacing, and empowering women are crucial for reducing the incidence of infant mortality in East Africa.